Revealing the Message of Spirituality in the Song “Tinggal Sertaku” Victory Song of Faith Number 148 - Trianus, Trianus; Batubara, Junita; Tika, Dewi (Jurnal Riset Ilmu Pendidikan, 2025)
The song “Tinggal Sertaku” in Nyanyian Kemenangan Iman (NKI) No. 148 is a work by Henry Francis Lyte that describes a spiritual request for God’s presence, especially when facing suffering and death. This study aims to uncover the message of spirituality in the song through a qualitative narrative approach with Charles Sanders Peirce’s semiotic method. Data were obtained through literature study, congregation interviews, and analysis of the song’s lyrics which include metric structure, rhyme, and style. The results of the analysis show that this song contains poetic symbols such as “twilight”, “dark”, and “death” which represent the fragility of human life and the eternity of God’s love. This song consists of four verses with varying rhyme patterns and long meter (10.10.10.10). This song is not just a prayer song, but also a declaration of faith in the presence of God who gives strength and hope in all life situations. In conclusion, “Tinggal Sertaku” has high theological and liturgical value and is relevant to be sung in various forms of Christian worship.